PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN, INSTITUSIONAL, KEBIJAKAN DIVIDEN, STRUKTUR ASET, PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, RISIKO BISNIS, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN UTANG PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Azalia Bonita; Hotman T Pohan (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2017)
The purpose of this research is to analyze the influence of insider ownership, institutional ownership, dividend policy, asset structure, profitability, firm growth, business risk and firm size to debt policy. Population in this research is non financial companies listed in Indonesia Stock Exchange during the study period of years 2011- 2013. The samples of this research are 61 nonfinancial companies. The multiple regression is statistic method which is used to test the research hypothesis. The results of this research show that profitability and firm size have significantly influence the debt policy. While insider ownership, institutional ownership, dividend policy, asset structure, firm growth, and business risk have not influence the debt policy.